Evaluating HARQ Protocols for Mobile and Interactive Applications in Underwater Acoustic Wireless Sensor Networks - Agnel Shyam Kumar C.; Christhu Raj M. R., (International Journal of Interactive Mobile Technologies (iJIM), 2026)
Underwater acoustic wireless sensor networks (UWSNs) play a vital role in supporting mobile and interactive applications such as real-time oceanographic monitoring, remote infrastructure inspection, and mission-critical maritime operations. However, the unique characteristics of underwater acoustic communication—including limited bandwidth, long propagation delays, and high error rates—pose significant challenges to achieving reliable, low-latency, and energy-efficient data delivery for mobile users. This paper presents a comparative performance evaluation of three hybrid automatic repeat request (HARQ) protocols, namely Type-I HARQ, Chase Combining HARQ (CC-HARQ), and Incremental Redundancy HARQ (IR-HARQ), within a realistic UWSN environment simulated using the RIVERBED platform. The analysis focuses on key performance metrics relevant to mobile and interactive applications, including packet delivery ratio, end-to-end delay, and energy consumption. Simulation results demonstrate that IR-HARQ provides superior reliability and energy efficiency, particularly under low signal-to-noise ratio conditions, making it well suited for interactive mobile access to underwater sensing data. By employing a realistic acoustic channel model rather than idealised assumptions, this study offers practical insights into the design of robust and adaptive communication mechanisms for mobile-centric UWSN deployments. The findings support the development of efficient underwater communication frameworks that enhance the quality of experience for mobile and interactive applications.